Natural hazards and disaster management : vulnerability and mitigation - Singh, R. B. (Ram Babu), 1955- (Jaipur : Rawat Publications, 2006)
Contributed articles.
Includes bibliographical references.
DEM
English.
Keywords: Emergency management; Hazard mitigation